2021
DOI: 10.3389/fspas.2021.700270
|View full text |Cite
|
Sign up to set email alerts
|

Ground Demonstration of the Use of Limnospira indica for Air Revitalization in a Bioregenerative Life-Support System Setup: Effect of Non-Nitrified Urine–Derived Nitrogen Sources

Abstract: Long-duration human space missions require considerable amounts of water, oxygen, and nutritious biomass. Additionally, the space vehicles must be well equipped to deal with metabolic human waste. It is therefore important to develop life-support systems which make these missions self-sufficient in terms of water, food, and oxygen production as well as waste management. One such solution is the employment of regenerative life-support systems that use biological and chemical/physical processes to recycle crew w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In some cases, ammonia and urea can be taken up directly by plants or microorganisms grown for food production. However, in a BLSS it is desirable to convert ammonia and urea to nitrate because it is a less volatile and less reactive molecule (Clauwaert et al, 2017;De Paepe et al, 2018;Sachdeva et al, 2021). MELiSSA C3 receives ammonia from C2 and urine from C5, and transforms both into nitrate for the plants and microalgae in C4 (Duatis and Moreno, 2009;2010).…”
Section: Compartment 3: Nitrification Of Ammonia and Ureolysismentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, ammonia and urea can be taken up directly by plants or microorganisms grown for food production. However, in a BLSS it is desirable to convert ammonia and urea to nitrate because it is a less volatile and less reactive molecule (Clauwaert et al, 2017;De Paepe et al, 2018;Sachdeva et al, 2021). MELiSSA C3 receives ammonia from C2 and urine from C5, and transforms both into nitrate for the plants and microalgae in C4 (Duatis and Moreno, 2009;2010).…”
Section: Compartment 3: Nitrification Of Ammonia and Ureolysismentioning
confidence: 99%
“…4.1.4 Compartment 4: food production 4.1.4.1 Compartment 4a: photoautotrophic cyanobacteria growth The edible microalgae Limnospira platensis and indica (previously Arthrospira platensis and indica) are cyanobacteria that consume nitrate and CO 2 that are produced in other compartments of the loop, and generate oxygen and food for the crew (Clauwaert et al, 2017;Alemany et al, 2019;Sachdeva et al, 2021). Limnospira is grown inside a gas lift photobioreactor with illumination and a gas injection system Poughon et al, 2021).…”
Section: Compartment 3b: Breakdown Of Urea By Ureolytic Heterotrophic...mentioning
confidence: 99%
“…Another species of cyanobacteria that is being considered for air revitalization, nitrate removal and edible biomass production in MELiSSA is Limnospira indica. In a recent 35-day ground study, L. indica was grown in a simplified closed-loop version of MELiSSA and the effect of urea, ammonium (the prominent nitrogen forms present in non-nitrified urine) and nitrate, on the oxygen production capacity of L. indica, was measured 106 . It was observed that cyanobacteria fed nitrate or urea could effectively reach the desired (set point) O 2 level of 20.3% and maintain ambient O 2 levels, while those fed ammonium could only reach a maximum O 2 level of 19.5% 106 .…”
Section: Atmosphere Revitalizationmentioning
confidence: 99%
“…In some cases, ammonia and urea can be taken up directly by plants or microorganisms grown for food production. However, in a BLSS it is desirable to convert ammonia and urea to nitrate because it is a less volatile and less reactive molecule (Clauwaert et al, 2017;De Paepe et al, 2018;Sachdeva et al, 2021). MELiSSA C3 receives ammonia from C2 and urine from C5, and transforms both into nitrate for the plants and microalgae in C4 (Duatis and Moreno, 2009;.…”
Section: Compartment 3: Nitrification Of Ammonia and Ureolysismentioning
confidence: 99%
“…4.1.4 Compartment 4: food production 4.1.4.1 Compartment 4a: photoautotrophic cyanobacteria growth The edible microalgae Limnospira platensis and indica (previously Arthrospira platensis and indica) are cyanobacteria that consume nitrate and CO 2 that are produced in other compartments of the loop, and generate oxygen and food for the crew (Clauwaert et al, 2017;Alemany et al, 2019;Sachdeva et al, 2021). Limnospira is grown inside a gas lift photobioreactor with illumination and a gas injection system (Garcia-Gragera et al, 2021;Poughon et al, 2021).…”
Section: Compartment 3b: Breakdown Of Urea By Ureolytic Heterotrophic...mentioning
confidence: 99%